New enhanced performance robust control design scheme for grid-connected VSI. (August 2016) - Syed, Asim H.; Abido, M.A.
Abstract: In this paper, a new method for intelligent robust control design is presented that achieves the best possible convergence rate of the system, utilizing the knowledge on the range of uncertain parameter. Thus resulting in enhanced stability and performance. The proposed method is applied to the grid-connected voltage source inverter (VSI) system with uncertainties in grid-impedance. Simulation and experimental results illustrate the efficacy of the proposed scheme. Comparison with existing methods shows that the proposed scheme can provide better reference tracking, stability for a wider uncertainty range, and improved transient and steady-state performance with low implementation cost. Highlights: A new approach to design intelligent robust controller is presented. The new method provides enhanced stability and performance of the system. The proposed method is applied for robust control design of grid-connected VSI. The controller is tested by real-time hardware-in-the-loop experiments. The performance of the controller is evaluated in comparison to existing methods.